Narodne manjšine - dejavnik povezovanja in konfliktov v državah tranzicije - Zupančič, Jernej (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2002)
The paper analyse the situation of ethnic minorities in transition countries. The role of national minorities changed in last two decades radically. In the past they were a object of strategic interesses and claims, contemporary thesis give them much more "kind" function of "connectors" among regions, states and nations. Unfortunatelly, in transition countries there still predominant their passive, or even worser, conflictual function. It seems that interethnic conflicts will play important role in the future, too.
Keywords: Europe; Evropa; mednarodno sodelovanje; narodne manjšine; obmejna območja; Slovenia; Slovenija; tranzicija